Economic assessment of conservation agriculture options in mixed crop-livestock systems in Brazil using farm modelling. (May 2016) - Alary, V.; Corbeels, M.; Affholder, F.; Alvarez, S.; Soria, A.; Valadares Xavier, J.H.; da Silva, F.A.M.; Scopel, E.
Abstract: Direct seeding mulch-based cropping (DMC) systems are often considered as an efficient way of combining ecological sustainability and economic viability while maintaining or increasing agricultural productivity. This paper describes a modelling analysis of the functioning of family farms in rural settlements of the agrarian reform in the Cerrados of Brazil. The aim was to assess the impact of the introduction of DMC systems with and without cover crops on crop-livestock management and net household income. A bio-economic farm model based on optimization of a utility function under multiple constraints was developed, capturing the interactions between livestock activities and the introduction of DMC systems. The model was run for six farms representing three farm types in the study area: 1) subsistence-oriented mixed crop-livestock farms; 2) market-oriented dairy farms; and 3) mixed crop-livestock farms, oriented to meat marketing. The following maize-based DMC systems were evaluated: a DMC system with mulch from residues of the previous maize crop and no cover crop, and two DMC systems with a fodder species, Brachiaria brizanta or Cajanus cajan, as cover crop. The simulated adoptability of DMC systems by farmers of the assentamentos depended to a large extent on the yields and feed quality of the fodder species. The modelling results suggested that DMC with C. cajan as cover crop was the best suitable option for all simulated farm types. This was mainly explained by its high feed value (expressed in crude protein content). Furthermore, in the process of intensification and specialization in dairy production, farmers were likely to shift from using maize for pig husbandry to feeding it to the dairy cows. The introduction of cover crops in the farm systems was a source of additional animal feed during the dry season that was cheaper than the purchase of feed concentrates, when the size of the dairy herd did not exceed a certain threshold. Highlights: Direct seeding mulch-based cropping (DMC) can be economically attractive for family farms in rural settlements of the agrarian reform in the Cerrados of Brazil. The adoption of DMC depends on fodder requirements on the farm and the price of feed concentrates. Bio-economic modelling allows a better understanding of the potential adoption of DMC in crop-livestock systems.